2006
DOI: 10.1002/jrs.1616
|View full text |Cite
|
Sign up to set email alerts
|

Stilbazolium merocyanine dye determination in different solutions, concentrations and colloids using SERS

Abstract: Surface-enhanced Raman scattering (SERS) measurements were carried out on stilbazolium merocyanine dye in methanol and pyridine solvents. Both solutions were measured in a series of concentrations covering a range of 5 × 10 −5 M to 5 × 10 −8 M. In these measurements, Ag and Au colloids were used, and the results have shown that Ag colloids yield better enhancement in the Raman spectra of this dye. Moreover, the effect of adding NaCl solution to the SERS samples was also studied. All measurements were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The experimental results are supported with DFT calculations. Earlier reports on the infrared reflection-absorption ( Itoh et al, 1992 ), resonance Raman intensity analysis ( Leng et al, 2004 ) and SERRS ( Tsukada et al, 1989 ; Mineo and Itoh, 1991 ; Pajchrowski et al, 2007 ) studies of MC have indicated the presence of trans -conformation on the metal surface, which is in agreement with this study. Thus, multi-faceted application of MCH + /MC in bio sciences, materials and chemistry has motivated the present study, with an aim to gain thorough understanding of its molecular level behavior on the nanostructured surface of SCFs.…”
Section: Introductionsupporting
confidence: 93%
“…The experimental results are supported with DFT calculations. Earlier reports on the infrared reflection-absorption ( Itoh et al, 1992 ), resonance Raman intensity analysis ( Leng et al, 2004 ) and SERRS ( Tsukada et al, 1989 ; Mineo and Itoh, 1991 ; Pajchrowski et al, 2007 ) studies of MC have indicated the presence of trans -conformation on the metal surface, which is in agreement with this study. Thus, multi-faceted application of MCH + /MC in bio sciences, materials and chemistry has motivated the present study, with an aim to gain thorough understanding of its molecular level behavior on the nanostructured surface of SCFs.…”
Section: Introductionsupporting
confidence: 93%
“…Pajchrowski et al 8 reported on using SERS to obtain Raman spectra of merocyanine dye at low concentrations (ca. 10 5 -10 8 M) in an attempt to find a new approach for further investigations of this dye.…”
Section: Applications Of Sersmentioning
confidence: 99%